Safety and efficacy of laparoscopic digestive tract nutrition reconstruction combined with conversion therapy for patients with unresectable and obstructive gastric cancer - Ye, Rong; Wang, Chuandong; Hu, Bo; Guan, Guoxian (Frontiers in Oncology, 2023)
Background: To explore the safety, efficacy, and survival benefits of laparoscopic digestive tract nutrition reconstruction (LDTNR) combined with conversion therapy in patients with unresectable gastric cancer with obstruction. Methods: The clinical data of patients with unresectable gastric cancer with obstruction who was treated in Fujian Provincial Hospital from January 2016 to December 2019, were analyzed. LDTNR was performed according to the type and degree of obstruction. All patients received the epirubicin + oxaliplatin + capecitabine regimen as conversion therapy. Results: Thirty-seven patients with unresectable obstructive gastric cancer underwent LDTNR, while thirty-three patients received chemotherapy only. In LDTNR group patients, the proportion of nutritional risks gradually decreased, the rate of severe malnutrition decreased, the proportion of neutrophil-lymphocyte ratio (NLR) <2.5 increased, the proportion of prognosis nutrition index (PNI) ≥45 increased, and the Spitzer QOL Index significantly increased at day 7 and 1 month postoperatively (P<0.05). One patient (6.3%) developed grade III anastomotic leakage and was discharged after the endoscopic intervention. The median chemotherapy cycle of patients in LDTNR group was 6 cycles (2-10 cycles), higher than that in Non-LDTNR group (P＜0.001) . Among those who received LDTNR therapy, 2 patients had a complete response, 17 had a partial response, 8 had stable disease, and 10 had progressive disease, which was significantly better than the response rate in Non-LDTNR group(P＜0.001). The 1-year cumulative survival rates of the patients with or without LDTNR were 59.5% and 9.1%. The 3-year cumulative survival rate with or without LDTNR was 29.7% and 0%, respectively (P＜0.001). Conclusions: LDTNR can improve the inflammatory and immune status, increase compliance with chemotherapy, and have potential benefits in improving the safety and effectiveness of and survival after conversion treatment.